Neuroinflammatory disorders of the brain and inner ear: a systematic review of auditory function in patients with migraine, multiple sclerosis, and neurodegeneration to support the idea of an innovative ‘window of discovery’ - Di Stadio, Arianna; De Luca, Pietro; Koohi, Nehzat; Kaski, Diego; Ralli, Massimo; Giesemann, Anja; Hartung, Hans-Peter; Altieri, Marta; Messineo, Daniela; Warnecke, Athanasia; Frohman, Teresa; Frohman, Elliot M. (Frontiers in Neurology, 2023)
Background: Hearing can be impaired by many neurological conditions and can even represent forme frustes of specific disorders. Auditory function can be measured by either subjective or objective tests. Objective tests are more useful in identifying which auditory pathway (superior or inferior) is most affected by disease. The inner ear's perilymphatic fluid communicates with the cerebrospinal fluid (CSF) via the cochlear aqueduct. Pathological changes in the contents of the CSF due to brain inflammation could, therefore, spread to and cause inflammation in the inner ear, This is a provisional file, not the final typeset article damaging inner hair cells and leading to hearing impairment identifiable on tests of auditory function. Methods: A systematic review of the literature was performed, searching for papers with case-control studies that analyzed the hearing function in patients with neuro-inflammatory and neuro-degenerative disorders. With data extracted from these papers, the risk of patients with neurologic disorders of having an altered DPOAE was then calculated. Results: Patients with neurologic disorders (headache, Parkinson disease, and Multiple Sclerosis) had a higher risk of having peripheral auditory deficits when compared to healthy individuals. Conclusions : Existing data lend credence to the hypothesis that neuroinflammation theoretically transmitted via the fluid exchange between this 'communication window' could be responsible for the disturbances in hearing described in neuroinflammatory disorders of the nervous system.